Foreign Language Anxiety in Bangladeshi University English Foundation Courses - Opshora Adhora (English Education: Jurnal Tadris Bahasa Inggris, 2026)
One of the most significant psychological factors influencing students' classroom learning experiences is anxiety in English as a Foreign Language (EFL). Both physical and emotional discomfort are common in many EFL classrooms, negatively affecting their participation and performance. As a result, one of the major challenges in foreign language education is creating a low-anxiety learning environment. The aim of this study is to explore how Bangladeshi university students develop foreign language anxiety and how it affects their English-speaking performance in foundation courses. To gain a deeper understanding of students’ experiences and perceptions, a qualitative research approach was adopted. Data were collected through classroom observations and semi-structured interviews. To generate descriptive data, qualitative methods were used that helped explain students’ behaviors, feelings, and attitudes toward English learning. To interpret the findings, thematic analysis helps, and triangulation guarantees the credibility of students and teachers in the classroom. The findings reveal that fear of negative evaluation, linguistic limitations, and social-cultural pressure are significant contributors to anxiety also the research shows that a Bengali medium educational background plays a significant role in shaping their foreign language anxiety. However, the instruments were validated and pilot tested for consistency. Based on the assumptions supported by the findings, the study may encourage the education system in Bangladesh to take effective measures to support Bengali-medium students in developing English as a second language.